Screening for pre‐eclampsia by maternal factors and biomarkers at 11–13 weeks' gestation. (11th July 2018) - Tan, M. Y.; Syngelaki, A.; Poon, L. C.; Rolnik, D. L.; O'Gorman, N.; Delgado, J. L.; Akolekar, R.; Konstantinidou, L.; Tsavdaridou, M.; Galeva, S.; Ajdacka, U.; Molina, F. S.; et al.
ABSTRACT: Objective: To examine the performance of screening for early, preterm and term pre‐eclampsia (PE) at 11–13 weeks' gestation by maternal factors and combinations of mean arterial pressure (MAP), uterine artery (UtA) pulsatility index (PI), serum placental growth factor (PlGF) and serum pregnancy‐associated plasma protein‐A (PAPP‐A). Methods: The data for this study were derived from three previously reported prospective non‐intervention screening studies at 11 + 0 to 13 + 6 weeks' gestation in a combined total of 61 174 singleton pregnancies, including 1770 (2.9%) that developed PE. Bayes' theorem was used to combine the prior distribution of gestational age at delivery with PE, obtained from maternal characteristics, with various combinations of biomarker multiples of the median (MoM) values to derive patient‐specific risks of delivery with PE at < 37 weeks' gestation. The performance of such screening was estimated. Results: In pregnancies that developed PE, compared to those without PE, the MoM values of UtA‐PI and MAP were increased and those of PAPP‐A and PlGF were decreased, and the deviation from normal was greater for early than late PE for all four biomarkers. Combined screening by maternal factors, UtA‐PI, MAP and PlGF predicted 90% of early PE, 75% of preterm PE and 41% of term PE, at a screen‐positive rate of 10%; inclusion of PAPP‐A did not improve the performance of screening. The performance of screening depended on the racial origin of the women; on screening by a combination of maternal factors, MAP, UtA‐PI and PlGF and using a risk cut‐off of 1 in 100 for PE at < 37 weeks in Caucasian women, the screen‐positive rate was 10% and detection rates for early, preterm and term PE were 88%, 69% and 40%, respectively. With the same method of screening and risk cut‐off in women of Afro‐Caribbean racial origin, the screen‐positive rate was 34% and detection rates for early, preterm and term PE were 100%, 92% and 75%, respectively. Conclusion: Screening by maternal factors and biomarkers at 11–13 weeks' gestation can identify a high proportion of pregnancies that develop early and preterm PE. © 2018 Crown copyright. Ultrasound in Obstetrics & Gynecology © 2018 ISUOG.